Pelaksanaan Pemberantasan Sarang Nyamuk Demam Berdarah Dengue Berbasis Perilaku Masyarakat di Kalipancur, Semarang - Yanuarita Tursinawati; Afiana Rohmani (Universitas Muhammadiyah Semarang, 2016)
Central Java Public Health Authorities have recorded that Semarang has the highest Incidence Rate (IR) of Dengue Hemorrhagic Fever (DHF) since 2009 to 2011. Ngaliyan district, part of Semarang region have suffered from DHF endemic. This research is conducted in Kalipancur, part of Ngaliyan district that aims to determine the behavioral domain of implementation of DHF mosquito nest eradication (3MPlus) based on the knowledge, attitudes and actions following by characteristic of thecommunity.This analytic observational research with cross sectional study involved 107 respondents. Primary data was collected through interviews using questionnaire related to knowledge, attitudes, actions and implementation of 3M Plus. Data was analyzed with chi square test, Confident Interval 95%.Results shows that 60.7% of community have low level of knowledge and 74.8% of them taking less actions regarding the implementation of 3M Plus. Nevertheless, 72% of respondents had a good attitudes. Both of knowledge (p=0,08) and actions (p=0,104) did not have a significant impact to the implementation of 3 M Plus. On the contrary, respondents attitudes (p=0,002) were found to be significant factor related to the implementation of 3M Plus. Therefore, provision of health information is needed to improve knowledge and actions of mosquito nest eradication of DHF. Keywords: Mosquito Nest Eradication, Dengue Hemorrhagic Fever, knowledge ,attitude, actions